Superresolution Modeling of Calcium Release in the Heart - Walker, Mark A. (Biophys J, 2014)
Stable calcium-induced calcium release (CICR) is critical for maintaining normal cellular contraction during cardiac excitation-contraction coupling. The fundamental element of CICR in the heart is the calcium (Ca(2+)) spark, which arises from a cluster of ryanodine receptors (RyR). Opening of these RyR clusters is triggered to produce a local, regenerative release of Ca(2+) from the sarcoplasmic reticulum (SR). The Ca(2+) leak out of the SR is an important process for cellular Ca(2+) management, and it is critically influenced by spark fidelity, i.e., the probability that a spontaneous RyR opening triggers a Ca(2+) spark. Here, we present a detailed, three-dimensional model of a cardiac Ca(2+) release unit that incorporates diffusion, intracellular buffering systems, and stochastically gated ion channels. The model exhibits realistic Ca(2+) sparks and robust Ca(2+) spark termination across a wide range of geometries and conditions. Furthermore, the model captures the details of Ca(2+) spark and nonspark-based SR Ca(2+) leak, and it produces normal excitation-contraction coupling gain. We show that SR luminal Ca(2+)-dependent regulation of the RyR is not critical for spark termination, but it can explain the exponential rise in the SR Ca(2+) leak-load relationship demonstrated in previous experimental work. Perturbations to subspace dimensions, which have been observed in experimental models of disease, strongly alter Ca(2+) spark dynamics. In addition, we find that the structure of RyR clusters also influences Ca(2+) release properties due to variations in inter-RyR coupling via local subspace Ca(2+) concentration ([Ca(2+)](ss)). These results are illustrated for RyR clusters based on super-resolution stimulated emission depletion microscopy. Finally, we present a believed-novel approach by which the spark fidelity of a RyR cluster can be predicted from structural information of the cluster using the maximum eigenvalue of its adjacency matrix. These results provide critical insights into CICR dynamics in heart, under normal and pathological conditions.